O fracasso escolar e a família: o que a clínica ensina? - Margaret Pires do Couto (2011)
This research had its main thrust in the study of the relationship between school failure and the family as of the analysis of cases tended in the university clinic of Centro Universitário Newton Paiva located in an area of the city of Belo Horizonte in which services are rendered to the community. The hypothesis which will be questioned in this work concerns the explanation of school failure resulting from family conflicts, specially dealing with the fathers absence within the family circle. In the discourse of the public school teachers of the area as well as responsible for directing their students to therapy at the school clinic, when problems learning problems are detected -, as a part of the family discourse of the childrens family, specially the mothers, the relation of failure with the paternal absence was evident. Besides that, the fathers fault and the absence of his authority in the family, was confirmed in the material gathered by the psychology students during the course of therapy, and presented at supervision sessions. It is this material which makes up the research data material analyzed in this work.The bibliographical research emphasized the psychoanalytical theory references more decidedly, the elaboration of Sigmund Freud, Jacques Lacan and of psychoanalysts of the Freudian persuasion, the school founded by Lacan, which claimed the Lacanian direction, as of the teachings of Jacques-Alain Miller. On the other hand, reading of the bibliography referring to the school failure produced during the last twenty years, with an emphasis on the indications pertaining to the relation of the school failure with the family and its problems. In the review of psychological, sociological, and educational literature, regarding school failure, can be verified when the family is pointed out as one of the causal factors of childrens learning problems, discussion has as its pivot points notions of the traditional family and the father as the head of the family .From that perspective, that which is presented and supported as the justification for the problems of the child in the school is the family dynamics, especially the destructuring of the family occasion brought on by the absence and omissions of the father. Going beyond that notion of the destructured family, that which was extracted as of the psychoanalytical formulation was the concept of the family as a responsible structure of the family as a symbolical structure responsible for the structural transmission of the symptom and the Lacanian formulation regarding the symptom of the child as capable representing the truth regarding the father, the mother or the family structure. The reference was searched was studied in clarifying what the paternal role is, the engraving of this for the subject and its correlative which is the transmission of the function of desire. Empirical research, which, in turn, carried out case studies as of the linical material presented by the trainee student, allowed the proving the destructured family syntagma as being capable filling or hushing up the need of subjectivity introducing itself in the relationship of the child with school learning. It also enabled the demonstration of that the principal effect for the child having therapy in the school/clinic is the operation of the separation regarding the discourse of the Otherparents, teachers, mental health specialists allowing the construction of knowing itself. A limit was observed with regards to the treatment of the childs symptom, which differs from the symptom of the Other- that is, school failure